2007
DOI: 10.1029/2006jc003641
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of landfast Antarctic and Arctic sea ice

Abstract: [1] We present final results from a program to measure the thermal conductivity of sea ice with in situ thermistor arrays using an amended analysis of new and previously reported ice temperatures. Results from landfast first-year (FY) ice near Barrow, Alaska, and McMurdo Sound, Antarctica, are consistent with predictions from effective-medium models but 10-15% higher than values from the parameterization currently used in most sea ice models. We observe no previously reported anomalous near-surface reduction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(125 citation statements)
references
References 30 publications
(81 reference statements)
3
114
0
2
Order By: Relevance
“…where z is the vertical (layer) coordinate, ρ the snow/ice density (assumed constant), E the snow/ice internal energy per unit mass (Schmidt et al, 2004), S the salinity, k the thermal conductivity (Pringle et al, 2007) and R the internal solar heating rate. The effect of brine inclusions is represented through the S and T dependency of E and k (e.g.…”
Section: Energymentioning
confidence: 99%
“…where z is the vertical (layer) coordinate, ρ the snow/ice density (assumed constant), E the snow/ice internal energy per unit mass (Schmidt et al, 2004), S the salinity, k the thermal conductivity (Pringle et al, 2007) and R the internal solar heating rate. The effect of brine inclusions is represented through the S and T dependency of E and k (e.g.…”
Section: Energymentioning
confidence: 99%
“…1b. The reduction of snow leads to an increase of May ice thickness of 0.12 m and to a decrease of September ice thickness of 0.06 m. Applying an increased conductivity coefficient for colder temperature (Pringle et al, 2007, CICE-mw-form-e-sd-bubbly) in addition reduces the error for CICE-free and CICE-ini to 20 less than 0.1 m. This modification increases winter ice growth, but it has no impact during summer.…”
Section: Improving Cice Simulation By Varying Model Physicsmentioning
confidence: 99%
“…We apply the bubbly conductivity formulation from Pringle et al (2007) Table 2. Sensitivity simulations exploring the impact of uncertainty in atmospheric forcing data.…”
Section: Y Y Cice-mw-form-ementioning
confidence: 99%
“…The thermal conductivity of snow is usually parameterized as a function of snow density, and that of sea ice, as a function of ice temperature and salinity (Maykut and Untersteiner, 1971). Pringle et al (2007) presented a new parameterization for sea ice on the basis of amended data analysis; heat conductivity was higher than that based on Maykut and Untersteiner (1971): by 5-10 % for multiyear ice and by 5-15 % for first-year ice. For snow, a micro-tomographic study by Calonne et al (2011) indicated that effective thermal conductivity increases with decreasing temperature, mostly following the temperature dependency of the thermal conductivity of ice.…”
Section: Heat Conductionmentioning
confidence: 99%